A Comprehensive Review of Honey-Containing Hydrogel for Wound Healing Applications - Andik Nisa Zahra Zainuddin; Nurul Nadhirah Mustakim; Farah Alea Rosemanzailani; Nur Izzah Md Fadilah; Manira Maarof; Mh Busra Fauzi (Gels)
Honey has long been recognized for its medicinal properties, particularly in wound healing. Recent advancements in material science have led to the development of honey-containing hydrogels, combining the natural healing properties of honey with the versatile characteristics of hydrogel matrices. These hydrogels offer numerous advantages, including high moisture retention, biocompatibility, and the controlled release of bioactive compounds, making them highly effective for wound healing applications. Hydrogels hold significant potential in advancing medical applications, particularly for cutaneous injuries. The diverse properties of honey, including antimicrobial, anti-inflammatory, and anti-eschar effects, have shown promise in accelerating tissue regeneration. According to studies, they are effective in maintaining a good swelling ratio index, Water Vapour Transmission Rate (WVTR), contact angle, tensile and elongation at break, in vitro biodegradation rate, viscosity and porosity analysis, lowering bacterial infections, and encouraging rapid tissue regeneration with notable FTIR peaks and SEM average pore sizes. However, limitations such as low bioavailability and inefficiencies in direct application reduce their therapeutic effectiveness at the wound site. Integrating honey into hydrogels can help preserve its wound healing mechanisms while enhancing its ability to facilitate skin tissue recovery. This review explores the underlying mechanisms of honey in wound healing management and presents an extensive analysis of honey-containing hydrogels reported in the literature over the past eight years. It emphasizes the physicochemical and mechanical effectiveness and advancements of honey-incorporated hydrogels in promoting skin wound healing and tissue regeneration, supported by evidence from both in vitro and in vivo studies. While honey-based therapies for wound healing have demonstrated promising outcomes in numerous in vitro and animal studies, clinical studies remain limited. Despite that, honey’s incorporation into hydrogel systems, however, offers a potent fusion of contemporary material technology and natural healing qualities, marking a substantial breakthrough in wound treatment.